2012
DOI: 10.1111/1574-6941.12008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA preservation methods for environmental bacterial community samples

Abstract: Field collections of environmental samples, for example corals, for molecular microbial analyses present distinct challenges. The lack of laboratory facilities in remote locations is common, and preservation of microbial community DNA for later study is critical. A particular challenge is keeping samples frozen in transit. Five nucleic acid preservation methods that do not require cold storage were compared for effectiveness over time and ease of use. Mixed microbial communities of known composition were creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 20 publications
5
95
0
1
Order By: Relevance
“…Whether this is a consequence of functional restructuring of the coral holobiont or a parallel response of the associated bacterial communities to differences in environmental conditions remains to be determined. Of note, in situ coral samples were preserved in RNAlater, whereas ex situ corals were flash frozen in liquid nitrogen, and it has been shown that RNAlater can bias samples regarding recovery of some bacterial taxa (Gray et al, 2013;Salter et al, 2014). Accordingly, some of the differences we found may be due to the different preservation methods used.…”
Section: Discussionmentioning
confidence: 92%
“…Whether this is a consequence of functional restructuring of the coral holobiont or a parallel response of the associated bacterial communities to differences in environmental conditions remains to be determined. Of note, in situ coral samples were preserved in RNAlater, whereas ex situ corals were flash frozen in liquid nitrogen, and it has been shown that RNAlater can bias samples regarding recovery of some bacterial taxa (Gray et al, 2013;Salter et al, 2014). Accordingly, some of the differences we found may be due to the different preservation methods used.…”
Section: Discussionmentioning
confidence: 92%
“…DNAgard, another product of Biomatrica, was created to permeate the cells and preserve the DNA in a proprietary solution. This system does not require refrigeration or freezing to retain the stability of the DNA for long-term storage (Table 1) (Gray et al 2013).…”
Section: Preservation With Biopolymersmentioning
confidence: 99%
“…Beside the step of cell poration, this technique also includes a step of freeze-drying, which is not readily available in field conditions. FTA technology (Whatman, GE Healthcare, Little Chalfont, UK) is based on the proprietary FTA cards that contain chemicals that lyse cells, denature proteins, and protect nucleic acids from damage (Table 1) (Gray et al 2013). A solution-based mix of high salts, RNAlater® (Ambion, Carlsbad, CA) (Table 1), preserves tissues for a long time depending on the temperature.…”
Section: Preservation With Biopolymersmentioning
confidence: 99%
See 2 more Smart Citations